Peran Mindfulness dalam Meningkatkan Regulasi Emosi pada Mahasiswa - Ira Lestari, Isma; Masfia, Irma; Ikhrom, Ikhrom (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
Students often face both academic and emotional pressures. Mental skills are important to adjust to the transition to stressful college life. One of the mental skills that students can apply is emotion regulation. Emotion regulation is a person's ability to control, identify, and act according to existing emotions. Mindfulness is the ability to be aware of what is happening in the present moment. This study aims to reveal the role of mindfulness in improving emotion regulation in college students. This research is based on a qualitative approach with in-depth interviews. In this study, it was found that mindfulness actively contributes to improving emotion regulation in university students.